Endovascular Treatment of a Temporal Bone Pseudoaneurysm Presenting as Bloody Otorrhea - Bien, Alexander G.; Cress, Marshall C.; Nguyen, Susan B.; Westgate, Steven J.; Nanda, Ashish (Journal of Neurological Surgery Reports, 2013)
Objective This case report is designed to illustrate an uncommon presentation of osteoradionecrosis (ORN) of the temporal bone and a treatment method for bloody otorrhea from a pseudoaneurysm of the internal carotid artery (ICA).Design This is a single patient case reportSetting University of Missouri-Columbia Hospital and Clinics.Participants The report describes a patient with a history of hypopharyngeal squamous cell carcinoma (SCCA) who was previously treated with chemoradiation therapy and salvage bilateral neck dissections and then presented in a delayed fashion with profuse, episodic bloody otorrhea. Computed tomography (CT) was consistent with ORN of the temporal bone. The patient underwent emergent cerebral angiography. A pseudoaneurysm of the cervicopetrous ICA was confirmed to be the source of the patient's bloody otorrhea. The lesion was treated by endovascular sacrifice of the ICA using the two-catheter coiling technique.Results The patient had no neurologic sequelae or further bleeding after treatment.Conclusions Bloody otorrhea is an uncommon presentation of ORN. Sacrifice of the internal carotid can be considered as a treatment when the source is pseudoaneurysmal.
Keywords: osteoradionecrosis; temporal bone; bloody otorrhea; endovascular coiling; radiation